Pengaruh Lokasi, Harga, dan Promosi terhadap Keputusan Pembelian - Pambudi, Firman Tulus; Ambarwati, Diana; Akbar, Taufik; Lestari, Veronika Nugraheni Sri; Nurmawati, Nurmawati; Sutariyono, Sutariyono (Commodities, Journal of Economic and Business, 2024)
This study discusses the influence of location, price, promotion and purchasing decisions at the Kharisma Agung supermarket. This study aims to determine the effect partially and simultaneously of, Price, Promotion on Purchasing Decisions at Kharisma Agung Supermarkets. To achieve this goal, the research method used is quantitative. The sampling technique used was proportionate stratified random sampling and the number of samples used was 100 respondents. The analysis technique uses multiple linear regression. The independent variables in this study are Location, Price, Promotion of Purchase Decisions while Purchasing Decisions as the dependent variable. The research data was obtained through a questionnaire given to customers who made purchases at Kharisma Agung Supermarkets on August 1 - 10, 2020, who were> 20 years old and <55 years old. The results show that Location, Price, and Promotion partially and simultaneously affect the Purchase Decision at Kharisma Agung Supermarkets. In this regard, Kharisma Agung Trenggalek Supermarkets should improve the location again because it has been proven to be able to influence the Purchase Decision of Kharisma Agung Supermarkets, Prices are also well maintained by supermarkets and increase the material provided in the Promotion to support customers in determining Purchasing Decisions.